Students’ mathematical problem-solving in HOTS based on learning interest - Muzakir, Muzakir; Kamid, Kamid; Yantoro, Yantoro (Universitas Jambi, Indonesia, 2026)
This study examines the association between students’ learning interest and their mathematical problem-solving ability in solving Higher Order Thinking Skills (HOTS) questions. The research employed a quantitative descriptive-correlational design involving 33 seventh-grade students at MTs Negeri 1 Merangin. Learning interest was measured using a Likert-scale questionnaire, and students were categorized into high, moderate, and low interest groups based on mean and standard deviation scores. Problem-solving ability was assessed through three HOTS items representing Bloom’s cognitive levels C4 (analysis), C5 (evaluation), and C6 (creation), evaluated using Polya’s problem-solving indicators. Data were analyzed using descriptive statistics and comparative analysis across interest categories. The results indicate that students with higher learning interest achieved better performance in problem-solving tasks. However, students’ performance was also influenced by the cognitive complexity of the HOTS items. The findings suggest that learning interest contributes positively to mathematical problem-solving ability.